Seismic anisotropy in northwestern Canada and eastern Alaska from shear wave splitting measurements - Witt, Derek Richard, author; Schutt, Derek, advisor; Aster, Richard, committee member; Breidt, Jay, committee member (Colorado State University. Libraries, 2017)
The Mackenzie Mountains are an actively uplifting and seismogenic mountain range that lies within the Yukon and Northwest Territories, Canada. The range is an eastward salient of the complexly deformed northern Canadian Cordillera, and lies ~500 kilometers away from and significantly off axis of the convergence direction of the Yakutat Indentor, a small oceanic-continental terrane that is subducting northward under North America in the Gulf of Alaska. To better assess the causes of the Mackenzie Mountains uplift and its broader relationship to deformation within the Northern Canadian Cordillera, shear wave splitting measurements have been performed on seismometers at over 150 locations within this region. Many of the measurements come from the Mackenzie Mountains Earthscope Project, a ~900 km NE-directed transect that spans from the complexly deformed coastal ranges near Skagway, Alaska, across the shortening axis of the Mackenzie Mountains, to the cratonic lithosphere at Great Bear Lake. This array is the first deployment of broadband seismometers within the Mackenzie Mountains and the current study is the first report from that array. Shear wave splitting provides a means to probe the seismic velocity anisotropy, and therefore the strain history, of the lithosphere and asthenosphere. Results indicate five distinct subregions of splitting behavior in our results: 1) chaotic, non-uniform splitting in the subduction zone complex; 2) fault-parallel fast axes along and between the Denali and Tintina dextral fault systems; 3) a short section of east-west fast axes near the British Columbia-Yukon border; 4) consistent fast axes aligned with North America absolute plate motion within the Canadian shield; and 5) the transitional inboard region between the Tintina fault and the Canadian shield, which includes the Mackenzie Mountains. Our findings support the hypothesis that shear from the Tintina and Denali faults penetrates the lithospheric mantle and has produced significant lithospheric anisotropy. The location of the strained mantle causing the observed anisotropy transitions from the lithosphere near the subduction zone and transpressional fault systems to the asthenosphere in the Canadian shield, where observations of asthenospheric flow are consistent with North America absolute plate motion.